Ravaging SARS-CoV-2: rudimentary diagnosis and puzzling immunological responses. (1st February 2021) - Mukherjee, Tapan Kumar; Malik, Parth; Maitra, Radhashree; Hoidal, John R.
Abstract: Introduction: In December 2019, the first COVID-19 case, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was reported in Wuhan, China. The SARS-CoV-2 rapidly disseminated throughout the world via community spread, acquiring pandemic status with significant fatality. Observations: Rapid SARS-CoV-2 diagnosis was soon perceived critical for arresting community spread and effective therapy development. Human SARS-CoV-2 infection can be diagnosed either by nucleic acid identification or specific antibody detection. Contrary to nucleic acid identification confirmed active SARS-CoV-2 infection; antibody detection confirms a past infection, even in asymptomatic subjects. SARS-CoV-2 specific antibodies augment the ability to effectively counter the virus. A crucial hurdle limiting the steadfast implementation of antibody detection is the time required for threshold B lymphocyte population generation. This process is dependent on precise antigen recognition and MHC class I molecules presentation. Conclusions: Thus, nucleic acid and antibody dependent tests complement each other in identifying human SARS-CoV-2 infection and shaping up subsequent immunological responses. This article discusses the complimentary association of nucleic acid identification (corresponding to an active infection) and antibody testing (the yester CoV-2 infection vulnerability) as the diagnostic and screening measures of SARS-CoV-2 infection. Highlights: Nucleic acid (RNA) identification and specific antibody detection against SARS-CoV-2 are the noted diagnostic mechanisms for screening human SARS-CoV-2 infection. While nucleic acid identification screens prevailing SARS-CoV-2 infection, detection of SARS-CoV-2 specific antibodies signifies a past infection, even in asymptomatic subjects. Antibodies against SARS-CoV-2 provide a potential therapeutic option via transfer from antibody rich plasma of a recovered subject to an infected individual. Nucleic acid identification may not absolutely confirm the infection because of frequent SARS-CoV-2 genome mutations and possible technical errors, while specific antibody detection also needs at least (8–14) days for detectable screening of B-cell generated antibodies. Nucleic acid and antibody tests are complementary to each other as an early stage diagnostic assay for SARS-CoV-2 infection and possible therapy (antibodies). Sufferers with a high clinical suspicion but negative RT-PCR screening could be examined via combined imaging and repeated swab test.